Imf Conditionality and Program Ownership : A Case for Streamlined Conditionality - Erbas, S. (IMF Working Papers; Working Paper, 2003)
Program conditionality and ownership are important considerations in the IMF's current rethinking of program design. This paper contributes to the literature by developing a theory of program conditionality and ownership on the basis of Cumulative Prospect Theory. The policymaker may value a set of programs, each with fewer conditions, more than an extended program with as many conditions. This valuation bias is greater in ambiguity (Knightian uncertainty) than under uncertainty. If greater valuation of a program engenders more explicit and implicit ownership, then programs with fewer conditions may have a better chance of success. Less is more.